The relationship between smartphone addiction, academic procrastination, and anxiety: evidence from a diary-based approach - Su, Miaoyan; Zhang, Jiayin; Xu, Yanhua; Hu, Jin (Acta psychologica, 2025)
To understand how academic procrastination, anxiety, and smartphone addiction are related, as well as the mechanisms underlying these relationships, this study constructed a mediation model to investigate the influence of college students' anxiety on their academic procrastination and the mediating effect of smartphone addiction. The study randomly selected 306 students from a university in Jiangxi Province and conducted a 10-day diary follow-up using the Smartphone Addiction Scale-Short Version, Academic Procrastination Scale and Anxiety Scale to capture daily dynamic data and distinguish between two-level effects. According to correlation analyses, academic procrastination was significantly impacted negatively by anxiety and significantly positively by smartphone addiction at the inter-individual level. At the intra-individual level, anxiety had a significant positive correlation with smartphone addiction and academic procrastination, and smartphone addiction had a significant positive correlation with academic procrastination. The internal level of individuals focuses on the variable fluctuations of the same subject at different time points, while the inter individual level focuses on the stable differences between different subjects. After adjusting for age, gender, and grade level, additional mediation analyses using SPSS 26.0 and Mplus 8.3 revealed that anxiety had a direct predictive influence on students' academic procrastination and an indirect predictive effect through smartphone addiction. The research demonstrated a causal link between academic procrastination and anxiety, providing a fresh viewpoint on the prevalence of anxiety, academic procrastination, and smartphone addiction in the student population and a theoretical basis for the development of interventions.